The attitudes of business majors toward the teaching of business ethics - Stewart, Karen (Journal of business ethics, 1996)
Business majors were tested for their attitudes toward the teaching of business ethics in university business education. Respondents indicated that they considered ethics an important part of a business curriculum and that they preferred integrating ethics into a number of different courses rather than taking a separate compulsory or elective ethics course. Ethical business practices were seen by respondents as increasing profit and return on investment and creating a positive work environment and public perception of the organization.